(untitled) - Vollhardt, K. Peter C. (New York, 1999)
The authors cover structure before function, introducing stereochemistry and spectroscopy early on, and the text is loaded with wide-ranging applications from the biological and environmental sciences and other disciplines. The emphasis is on the most important reactions and on helping students develop synthetic strategy techniques for exploring chemical structures. New features include more on acid-base chemistry, new discussions of stereoscopic techniques and 20% more problems, with the addition of new-style Team and Pre-professional Problems.
Keywords: Chemistry, Organic,Hóa học, hữu cơ